2009
DOI: 10.1002/bsl.850
|View full text |Cite
|
Sign up to set email alerts
|

Violent offenses associated with co‐occurring substance use and mental health problems: Evidence from CJDATS

Abstract: The present study examines the relationship between substance use, mental health problems, and violence in a sample of offenders released from prison and referred to substance abuse treatment programs. Data from 34 sites (n = 1,349) in a federally funded cooperative, the Criminal Justice Drug Abuse Treatment Studies (CJDATS), were analyzed. Among parolees referred to substance abuse treatment, self-reports for the six-month period before the arrest resulting in their incarceration revealed frequent problems wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
(56 reference statements)
2
16
1
Order By: Relevance
“…Personality problems are also prevalent (Nederlof, van der Ham, Dingemans, & Oei, 2010). Detained adolescents with mental health problems are at increased risk of a range of adverse outcomes including premature mortality, suicide and death from other causes Rodway, Norrington-Moore, While et al, 2011), drug and alcohol problems (Chassin, Knight, Vargas-Chanes, Losoya, & Naranjo, 2009;McClelland, Elkington, Teplin, & Abram, 2004;Neighbors, Kempton, & Forehand, 1992;Palmer, Jinks, & Hatcher, 2010;Sacks et al, 2009), and increased rates of reoffending (Hollander & Turner, 1985;Ramchand, Morral, & Becker, 2009;Walter, Wiesbeck, Dittmann, & Graf, 2011). Thus, documenting the extent of psychiatric morbidity in different juvenile justice settings can assist in service development, setting priorities for funding, resource allocation, and treatment interventions (Brink, 2005;Quinn & Shera, 2009;Rodway, Norrington-Moore, Appleby, & Shaw, 2011;Sirdifield, Gojkovic, Brooker, & Ferriter, 2009).…”
Section: Psychiatric Disorders In Adolescent Boys In Detention: a Prementioning
confidence: 95%
“…Personality problems are also prevalent (Nederlof, van der Ham, Dingemans, & Oei, 2010). Detained adolescents with mental health problems are at increased risk of a range of adverse outcomes including premature mortality, suicide and death from other causes Rodway, Norrington-Moore, While et al, 2011), drug and alcohol problems (Chassin, Knight, Vargas-Chanes, Losoya, & Naranjo, 2009;McClelland, Elkington, Teplin, & Abram, 2004;Neighbors, Kempton, & Forehand, 1992;Palmer, Jinks, & Hatcher, 2010;Sacks et al, 2009), and increased rates of reoffending (Hollander & Turner, 1985;Ramchand, Morral, & Becker, 2009;Walter, Wiesbeck, Dittmann, & Graf, 2011). Thus, documenting the extent of psychiatric morbidity in different juvenile justice settings can assist in service development, setting priorities for funding, resource allocation, and treatment interventions (Brink, 2005;Quinn & Shera, 2009;Rodway, Norrington-Moore, Appleby, & Shaw, 2011;Sirdifield, Gojkovic, Brooker, & Ferriter, 2009).…”
Section: Psychiatric Disorders In Adolescent Boys In Detention: a Prementioning
confidence: 95%
“…Some studies have suggested that the combination of mental illness with substance abuse and non-compliance with medication increases the risk of violent behavior and CJS involvement beyond the risk that is directly due to either mental illness or substance abuse alone (Steadman et al 1998;Elbogen and Johnson 2009;Rasanen et al 1998). However, Sacks et al (2009) found that co-occurring disorders generally did not increase the risk of violence beyond the main effects of specific mental disorders. Other studies that have addressed this issue appear not to have investigated the degree to which the risk of violence increased above and beyond the risk engendered by the main effects of mental health and substance abuse diagnoses by themselves (Swanson et al 1996) or only examined how substance abuse increased the risk of violence among individuals with a mental illness (Cuffel et al 1994;Fulwiler et al 1997;Swanson et al 2006;Swartz et al 1998).…”
Section: Discussionmentioning
confidence: 95%
“…While some authors (12)(13)(14)(15)(16) advance the notion that serious mental illness (psychosis and mood disorders) may explain violent behavior, others fail to establish a causal relation between suffering a mental disorder and manifesting violent behavior (17). In the literature there is greater consensus regarding the relationship between violent behavior and the use of drugs in association with a mental disorder (7,13,15,18,19). With 973 serious mental illnesses such as schizophrenia and bipolar disorder, the use of drugs increases the likelihood of violence (20).…”
Section: Introductionmentioning
confidence: 99%